Implementasi Mata Kuliah PHS: Penanaman Tanaman Obat Keluarga di SMP Negeri 2 Gorontalo - Haryani, Meri; Hatibie, Moh. Apriansyah; Setiawan, Budi; Malik, Haikal; Antu, Rehan; Didipu, Meliskawati; Irawan, Safri; Buhungo, Mahmudin (Universitas Negeri Gorontalo, 2025)
The implementation of the Health Behavior course (PHS) at SMPN 2 Gorontalo involves the application of Family Medicinal Plants (TOGA) as part of health education. This program utilizes the available land around the school to grow various medicinal plants with healing properties. The plants taught and cultivated at the school include turmeric, ginger, galangal, temulawak, and kaffir lime. Through this activity, students are provided with an understanding of the benefits of family medicinal plants in treating common illnesses such as colds, coughs, and indigestion. Additionally, they are taught how to plant and care for medicinal plants, which can be used for simple treatments and natural cosmetic products. This activity aims to enhance students' awareness of the importance of maintaining health through natural and independent methods, as well as introducing them to agricultural practices beneficial for health.